Kajian Literatur: Implementasi Performance-Based Budgeting Pada Institusi Pendidikan Tinggi di Indonesia - Lorensius Lorensius; Warman Warman; Yunata Tresia (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
This paper discusses the application of performance-based budgeting in higher education institutions in Indonesia. This study uses a literature review method with narrative analysis to deepen knowledge about performance-based budgeting. The conclusion that can be drawn from this study is that the implementation of performance-based budgeting plays an important role in realizing a quality higher education institution. To implement performance-based budgeting, universities must consider management competencies, organizational commitment, reward systems, and higher education quality. This paper provides a different perspective to understand the application of performance-based budgeting by integrating institutional management theory and organizational theory in setting organizational goals.